Higher Education in the Age of Artificial Intelligence - A. V. Rezaev; A. M. Stepanov; N. D. Tregubova (Высшее образование в России, 2024)
The breakneck expansion of artificial intelligence (AI) technologies in recent years has attracted the attention of higher education researchers. However, their curiosity often comes down to using specific AI tools, such as text and image generators, translators, and personal assistants in the educational process. This paper considers a broader question: what fundamental problems and challenges does the penetration of AI technologies into human lives originate for higher education? The authors offer a working definition of what it means to give/receive higher education in the age of AI. This definition identifies five critical characteristics of higher education: 1) the professor and the student continue to be in a subject-subject relationship and learn from each other; 2) higher education should prepare for life in conditions of “human-machine” interdependence; 3) these conditions imply choice in situations of uncertainty; 4) the spread of AI technologies brings enormous opportunities and 5) almost unpredictable dangers, risks and threats to humans. The authors consider general principles and specific problems associated with entering AI tools into society and higher education. They discuss the inevitability of the evolvement of “machine-machine interdependence” related to the development of autonomous agents. In conclusion, several theses and counter-theses summarize the article’s argumentation.